2015
DOI: 10.1073/pnas.1517847112
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of diabetic wound healing using a novel protease–anti-protease combination therapy

Abstract: Nonhealing chronic wounds are major complications of diabetes resulting in >70,000 annual lower-limb amputations in the United States alone. The reasons the diabetic wound is recalcitrant to healing are not fully understood, and there are limited therapeutic agents that could accelerate or facilitate its repair. We previously identified two active forms of matrix metalloproteinases (MMPs), MMP-8 and MMP-9, in the wounds of db/db mice. We argued that the former might play a role in the body's response to wound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
159
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(171 citation statements)
references
References 38 publications
11
159
1
Order By: Relevance
“…SB-3CT and ND-322 have also been shown to cross the blood/brain barrier[27, 28], indicating that ND-322 could potentially be used for the treatment of melanoma brain metastasis, which affects up to 40% of metastatic melanoma patients[29]. Finally, in our study ND-322 was well tolerated by mice, similarly to what was previously shown in a model of wound healing[30] This aspect is important as earlier trials with broad-spectrum MMP inhibitors failed mostly due to severe side effects such as musculoskeletal pain and inflammation, accompanied by negligible anti-cancer effects [10, 11]. …”
Section: Discussionsupporting
confidence: 86%
“…SB-3CT and ND-322 have also been shown to cross the blood/brain barrier[27, 28], indicating that ND-322 could potentially be used for the treatment of melanoma brain metastasis, which affects up to 40% of metastatic melanoma patients[29]. Finally, in our study ND-322 was well tolerated by mice, similarly to what was previously shown in a model of wound healing[30] This aspect is important as earlier trials with broad-spectrum MMP inhibitors failed mostly due to severe side effects such as musculoskeletal pain and inflammation, accompanied by negligible anti-cancer effects [10, 11]. …”
Section: Discussionsupporting
confidence: 86%
“…Several natural compounds have been proposed for the treatment of hard-to-heal wounds, such as Manuka honey, 23 13,32 or cells, 58 often requiring considerations with regard to activity and release of payload as well as customisation of material format.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 In contrast to skin substitutes, 6 wound dressings are temporarily applied to the wound bed, in order to ensure a defined environment in terms of moisture (to minimise the risk of tissue maceration) and exudate management (to retain growth factors, MMPs and specific cells key to healing). 7,8 Furthermore, an ideal wound dressing should (i) provide thermal insulation and oxygen exchange; (ii) protect damaged tissue from secondary infections and bacterial contamination; (iii) display low adherence in situ to enable complete dressing removal without debris formation and integration with the host tissue; (iv) control activity of up-regulated MMPs, such as MMP-9, 9,10,11,12,13,14,15,16,17 in order to promote wound healing; (v) not induce any toxic response to tissue microenvironment. Although these requirements can be individually provided by many existing commercial dressings, such controlled multi-functionality is still challenging to accomplish in a single, soluble factor-free material system.…”
mentioning
confidence: 99%
“…Moderate oxidation and inflammation are conducive to wound healing through induction of proliferation and migration of skin keratinocytes and fibroblasts. However, their excessive or persistent status can hinder wound healing by activation of MMPs or induction of neutrophil NETosis and damage extracellular matrix (ECM) [23, 24]. Therefore, we want to further investigate whether the effects of NAC on MGO-induced inflammatory injury are associated with the inhibition of AGEs/RAGE signal.…”
Section: Introductionmentioning
confidence: 99%